Pengembangan Media Pembelajaran Berbasis E-Learning Portable Moodle Materi Sistem Koordinasi Untuk SMA Kelas XI IPA - Nurlinah, Nurlinah; Adnan, Adnan; Muhiddin P., Muhiddin P. (Universitas Negeri Makassar, 2018)
Abstract. This study aims to determine the validity and practicality of moodle (poodle) portable learning media in biology learning. This research is a development research with 4D models. The subjects of this study were students of class XI IPA 1 and XI IPA 2 Senior High School of Pangkajene 20, Pangkep and Biology teachers. This study was conducted for 4 meetings for media trials by researchers and Biology teachers. The collection technique was to validate the expert validator first, then share the questionnaire responses of the teachers and student responses to test the practicality of the media that has been made. The results of expert validation showed that media development products have valid criteria based on assessment by material experts at 4.3 and media experts at 4.6. Field tests were carried out for students of Senior High School of Pangkajene 20 and biology teachers as the users of media products, and obtained criteria based on the acquisition of scores percentage of assessments in each trial amounted to 79.62% for student responses and 90% for teacher responses. Based on the data analysis in this study, it was concluded that the results of the development of poodle-based media obtained valid and practical criteria for use in biology learning. Keywords: media, portable, moodle, valid, practical.